2014
DOI: 10.4103/0972-124x.131319
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of subgingivally delivered xanthan-based chlorhexidine gel and herbal extract gel in the treatment of chronic periodontitis

Abstract: Background:Local drug delivery agents can effectively deliver the antimicrobial drugs in bactericidal concentration, and have shown improved clinical outcomes when used as an adjunct to mechanical therapy. The aim of this study was to evaluate the efficacy of a xanthan-based chlorhexidine gel versus herbal extracts’ gel as an adjunct to periodontal therapy in the treatment of chronic periodontitis.Materials and Methods:A total of 150 sites, age group of 30-50 years, periodontal pockets measuring 5-8 mm and dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 13 publications
0
33
0
1
Order By: Relevance
“…One study showed that the test group presented a significant greater BOP change than control group; however, there were no differences between groups as regards PI and GI . Another study found a greater reduction in PI and GI on the test group . One study did not find differences in the GI between test and control groups and another did not find differences in BOP change and PI between groups…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…One study showed that the test group presented a significant greater BOP change than control group; however, there were no differences between groups as regards PI and GI . Another study found a greater reduction in PI and GI on the test group . One study did not find differences in the GI between test and control groups and another did not find differences in BOP change and PI between groups…”
Section: Resultsmentioning
confidence: 97%
“…Initially, 164 patients with chronic periodontitis were enrolled, and 154 (93.9%) completed the follow‐up. Just 1 study included smokers and 6 others excluded them …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations